OPTIMASI DESAIN PENCAHAYAAN RUANG KELAS SMA SANTA MARIA SURABAYA - Dora, Purnama Esa (Institute of Research and Community Outreach - Petra Christian University, 2011)
Lighting is one of the most important aspect of designing a room. A good school should be designed so that it can increase the effectivity of the learning process. The lighting design standard of classrooms in Indonesia is 250 luxÂ â€“ 350 lux. Meanwhile, the type of lamp recommended in a classroom is one with a neutral white lamp color that could blend well with natural daylight. The schools in Surabaya that occupies old Dutch colonial buildings today generally have problems in lighting intensity. The evaluation result in SMA Santa Maria Surabaya on January 9, 2010 showed that all of the classrooms have lighting problems since they did not fullfil classroom lighting standards. Among 19 classrooms evaluated, 13 classrooms didnâ€™t fullfil the standard (too dark) and the other 6 were overbright. Hence, the lighting designs in these schools need to be corrected to solve vision problems. This research was done using the quantitative method of approach, and correction will be performed with simulation and optimation method to achieve the optimum lighting standard.